Two-stage fermentation process for enhanced mannitol production using Candida magnoliae mutant R9 - Savergave, Laxman S.; Gadre, Ramchandra V.; Vaidya, Bhalchandra K.; Jogdand, Vitthal V. (Bioprocess and Biosystems Engineering, 2013)
Mutants of Candida magnoliae NCIM 3470 were generated by treatment of ultra-violet radiations, ethyl methyl sulphonate and N-methyl-N'-nitro-N-nitrosoguanidine. Mutants with higher reductase activity were screened by means of 2,3,5-triphenyl tetrazolium chloride agar plate assay. Among the screened mutants, the mutant R9 produced maximum mannitol (i.e. 46 g l(-1)) in liquid fermentation medium containing 250 g l(-1) glucose and hence was selected for further experiments. Preliminary optimization studies were carried out on shake-flask level which increased the mannitol production to 60 g l(-1) in liquid fermentation medium containing 300 g l(-1) glucose. A two-stage fermentation process comprising of growth phase and production phase was employed. During the growth phase, glucose was supplemented and aerobic conditions were maintained. Thereafter, the production phase was initiated by supplementing fructose and switching to anaerobic conditions by discontinuing aeration and decreasing the speed of agitation. The strategy of two-stage fermentation significantly enhanced the production of mannitol up to 240 g l(-1), which is the highest among all fermentative production processes and corresponds to 81 % yield and 4 g l(-1) h(-1) productivity without formation of any by-product.
Keywords: Candida magnoliae; D-Mannitol; Mutagenesis; Strain improvement; Two-stage fermentation